Aproximate integration and construction of a bounder layer of equation on the Banach's space - Osipov, V. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Б. Осипов. Асимптотическое интегрирование и построение пограничного слоя для уравнения в банаховом пространствеV. Osipovas. Asimptotinis integravimas ir pasienio sluoksnio konstravimas lygčiai Banacho erdvėje